Effectiveness of the Cover–Copy–Compare (CCC) Procedure in Developing Fluency in Basic Multiplication Facts for a Student with Mathematics Difficulties - Uysal, Halil; Uçar, Ahmet Serhat; Gizir, Zuhal (Journal of Cultural Analysis and Social Change, 2026)
In this study, the effectiveness of the cover–copy–compare (CCC) procedure in building fluency with basic multiplication facts was examined for a student with a learning disability who performed below peers in mathematics. The study also sought to determine whether the student (a) maintained fluency on the mastered facts at 4-, 8-, and 12-day follow-ups; (b) generalized performance on these facts in line with the commutative property of multiplication; (c) approached the endline fluency levels obtained from typically developing peers; and (d) reported favorable views of the intervention. One 11-year-old student with a diagnosed learning disability receiving inclusive education participated. A single-case research design—specifically, a multiple-probe design—was employed. Findings indicated that CCC was effective in increasing the students’ fluency with basic multiplication facts, that these gains were maintained at 4, 8 and 12 days post-instruction, and that high levels of generalization were observed with respect to the commutative property. By the end of the study, the students’ fluency levels on basic multiplication facts approximated those of their typically developing peers. Social validity data further showed that the student viewed the CCC intervention as adequate and appropriate.